Tailoring Cathode–Electrolyte Interface for High-Power and Stable Lithium–Sulfur Batteries - Liu, Mengting; Hu, Ling‑Jiao; Guan, Zhao‑Kun; Chen, Tian‑Ling; Zhang, Xin‑Yu; Sun, Shuai; Shi, Ruoli; Jing, Panpan; Wang, Peng‑Fei (Nano-Micro Letters, 2024)
Global interest in lithium–sulfur batteries as one of the most promising energy storage technologies has been sparked by their low sulfur cathode cost, high gravimetric, volumetric energy densities, abundant resources, and environmental friendliness. However, their practical application is significantly impeded by several serious issues that arise at the cathode–electrolyte interface, such as interface structure degradation including the uneven deposition of Li2S, unstable cathode–electrolyte interphase (CEI) layer and intermediate polysulfide shuttle effect. Thus, an optimized cathode–electrolyte interface along with optimized electrodes is required for overall improvement. Herein, we comprehensively outline the challenges and corresponding strategies, including electrolyte optimization to create a dense CEI layer, regulating the Li2S deposition pattern, and inhibiting the shuttle effect with regard to the solid–liquid–solid pathway, the transformation from solid–liquid–solid to solid–solid pathway, and solid–solid pathway at the cathode–electrolyte interface. In order to spur more perceptive research and hasten the widespread use of lithium–sulfur batteries, viewpoints on designing a stable interface with a deep comprehension are also put forth. Highlights: 1 This review delves into the mechanism of the state-of-the-art lithium–sulfur batteries from a novel perspective of cathode–electrolyte interface. 2 It provides extensive strategies to construct a stable cathode–electrolyte interphase layer and improve the uneven deposition of Li2S, enhancing the stability of the interface structure. 3 It proposes an in-depth and comprehensive research on how to inhibit the shuttle effect at the cathode–electrolyte interface with regard to distinct reaction pathways.